2003
DOI: 10.1097/00003226-200304000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Corneal Anatomy in a Pair of Monozygotic Twins Due to Continuous Contact Lens Wear

Abstract: The differences between the monozygotic twins seem to confirm that daily use of soft contact lenses can modify normal corneal anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…The impact of soft contact lenses on the cornea has been demonstrated by a monozygotic twin study. 72 Indeed, the majority of work on this subject (including this study) supports a degree of corneal thinning in association with contact lens within normal corneas. 73 To distinguish the effects of contact lens wear from the disease process of keratoconus, ideally, true unilateral keratoconics might be required to wear contact lenses in both eyes.…”
Section: 39supporting
confidence: 52%
“…The impact of soft contact lenses on the cornea has been demonstrated by a monozygotic twin study. 72 Indeed, the majority of work on this subject (including this study) supports a degree of corneal thinning in association with contact lens within normal corneas. 73 To distinguish the effects of contact lens wear from the disease process of keratoconus, ideally, true unilateral keratoconics might be required to wear contact lenses in both eyes.…”
Section: 39supporting
confidence: 52%
“…35 The implementation of a rigorous Orbscan screening protocol Change in height above best-fit sphere may reduce the low incidence of severe, detrimental keratectasia after laser refractive surgery. 93,94 Additional studies using the pachymetry measurements of Orbscan have shown corneal thinning in dry eye, 95 prolonged contact lens use, 29,96 Marfan's syndrome, 97 and ocular rosacea. 98 Additionally, Orbscan topography has been used to record population trends with respect to topography, 99,100 hypoxia, 101 anesthesia, 102 tear-film effects, 103 white-to-white corneal diameters, 104 and central islands following laser refractive surgery.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…Sanchis-Gimeno et al 17 studied differences in endothelial cell density in a pair of 31-year-old monozygotic female twins; one had been wearing contact lenses for the past 15 years and the other had never worn contact lenses. Lower central corneal endothelial cell densities were found in both eyes of the monozygotic contact lens-wearing twin.…”
Section: Normal Endothelial Cell Densitymentioning
confidence: 99%